Profil migran masuk di enam kota besar, Medan, Bandung, Surabaya, Jakarta, Semarang, Ujung Pandang : hasil survei urbanisasi 1995 (Seri S, 1997)
Statistics on migrants in six cities of Indonesia; results of the 1995 urbanization survey.